Indigenous Knowledge on Rodent Management of the Ao-Nagas of Mokokchung District, Nagaland - Amri, Talisosang; Longkumer, J. (International Journal of Bio-resource and Stress Management, 2018)
The study of indigenous knowledge on rodent management of the Ao-Nagas of Mokokchung district, Nagaland, India was conducted during the period 2011–2012. Six villages covering the six ranges of Mokokchung District were selected purposively for the study and taking 16 respondents each from a village, making 96 respondents in total. 68% of the respondents still followed indigenous methods and while the rest 32% followed modern management. Eight independent variables were selected for the study viz., age, sex, educational status, marital status, farming experience, mass media contact and extension agency contact and two dependent variables viz., Perceived Effectiveness of indigenous control method and extent of adoption of modern control method. In the study, it was found that 37.50% of the respondents belong to the category of 51–60 years. 35.42% of the respondents had primary level of school education. Majority of the respondents (60.41%) had more than 20 years of farming experience. 47.92% of the respondents had no mass media exposure and 67.71% of the respondents had no contact with the extension agencies. Five indigenous physical methods of rodent management were identified and documented viz., Longnen, Merang sang, Konglen, Tsüngtem and Tongi.